SENAM OTAK LEBIH MENINGKATKAN KESEIMBANGAN DINAMIS DARIPADA SENAM KESEGARAN JASMANI (2008) PADA ANAK USIA 7-8 TAHUN DI KECAMATAN SIMPANG TERITIP BANGKA BARAT - Hapy Ardiaviandaru Siamy; J.Alex Pangkahila; Muh. Irfan (Sport and Fitness Journal, 2015)
Nowadays , decreasing of physical activity of children were increasing therisk of falling and injury. The Provision of physical activity of children years willincrease the balancing ability and reduced risk of fall. Dinamic balance started atage 7-8 years. Gymnastics is a physical activity which helps to optimize the brainfunction, one of them is dynamis balance. This study aims to determine thephysical training of brain gyms were better to improve the dynamic balancingthan Senam Kesegaran Jasmani (SKJ) 2008 in children of age 7-8 years old.Thisstudy used true experimental method with pre-test and post design. Experimentwas conducted in SD Negeri 8 Simpang Teritip, SD Negeri 11 Simpang Teritip,SD Negeri 15 Simpang Teritip Bangka Barat. Group control was givenintervention SKJ 2008 consisted of 38 boys and 41 girls, while in the treatmentgroup was given brain gyms intervention consisted of 35 boys and 44 girls. Theexercises was conducted 3x per week for 6 weeks. Balance beam walking test wasused to measure the dynamic balancing. The results of using Wilcoxon test in thecontrol group gained an average of dynamic balancing before trained the SKJ2008 was 2.95 ± 0.354 and after trained the SKJ 2008 was 4.15 ± 0.949 with p =0.000 (p <0.05). Whereas in the treatment group the mean of dynamic balancebefore brain gym was 2.89 ± 0.358 and after brain gym was 4.97 ± 0.225 with p =0.000 (p <0.05). Different mean of dynamic balancing among group control andtreatment were tested using the Mann Whitney was obtained p value = 0.000 (p<0.05) with a mean value of dynamic balance after treatment in the treatmentgroup of brain gym was 4.97 ± 0.225 was heigest than the group of SKJ 2008 was4.15 ± 0.949. The conclusion of SKJ 2008 and brain gyms that can improve thedynamic balancing in children of age 7-8 years old, however brain gym was moreimprove the dynamic balance than SKJ 2008 in children of age 7-8 years old.